Analysis of Out of Court Medical Dispute Resolution According to the Laws and Regulations Applicable in Indonesia - Ariko Rahmat Putra; Noormartany Noormartany; Dony Septriana Rosady (SOEPRA, 2021)
Abstract: The medical profession is a noble profession because it upholds human values. In carrying out the medical profession, there is a legal relationship between doctors and patients, both civil, criminal and state administration. In civil terms, if one of the parties defaults, it will cause a medical dispute. Medical dispute resolution is not only done in court but can also be done outside the court.The purpose of this research is to find out alternative medical dispute resolution outside the court in accordance with the prevailing laws and regulations.This research is juridical-normative research. This research describes medical dispute resolution in Indonesia based on the prevailing laws and regulations in Indonesia. Then, analyze each medical dispute resolution option contained in statutory regulations.The doctor-patient relationship in terms of civil law is a therapeutic agreement. If in the agreement one of the parties is in default, such as a doctor who has committed an act that is detrimental to the patient, it can lead to a medical dispute. Civil medical dispute resolution is not only resolved in court but can also be carried out outside the court through several mechanisms, namely consultation, negotiation, mediation, conciliation and expert opinion.Keyword: The Settlement, Medical Dispute, Outside the Court Abstrak: Profesi dokter merupakan profesi yang mulia karena menjunjung tinggi nilai kemanusiaan. Dalam melaksanakan profesi kedokteran terdapat hubungan hukum antara dokter dan pasien, baik secara perdata, pidana, maupun tata usaha negara. Secara perdata, jika salah satu pihak melakukan wanprestasi maka menimbulkan sengketa medik. Penyelesaian sengketa medik tidak hanya di dalam pengadilan, tetapi juga dapat dilakukan di luar pengadilan.Tujuan penelitian ini untuk mengetahui alternatif penyelesaian sengketa medik di luar pengadilan yang sesuai dengan peraturan perundang-undangan yang berlaku.Penelitian ini merupakan penelitian yuridis-normatif. Penelitian ini mendeskripsikan penyelesaian sengketa medik di Indonesia berdasar atas peraturan perundang-undangan yang berlaku di Indonesia. Kemudian, menganalisis setiap pilihan penyelesaian sengketa medik yang terdapat di peraturan perundang-undangan.Hubungan dokter-pasien ditinjau dari hukum perdata merupakan perjanjian terapeutik. Jika dalam perjanjian salah satu pihak melakukan wanprestasi seperti dokter yang melakukan tindakan yang merugikan pasien maka dapat menimbulkan sengketa medik. Penyelesaian sengketa medik secara perdata tidak hanya diselesaikan dipengadilan saja, tetapi juga dapat dilakukan di luar pengadilan melalui beberapa mekanisme, yaitu konsultasi, negosiasi, mediasi, konsiliasi, dan pendapat ahli.Kata Kunci: Penyelesaian, Sengketa Medik, Luar Pengadilan